Utility of a whole blood single platelet counting assay to monitor the effects of tirofiban in patients with acute coronary syndromes scheduled for coronary intervention - Siotia, Anjan; Buckland, Robert; Judge, Heather M.; Sastry, Padmini; Storey, Robert F. (Thrombosis and Haemostasis, 2006)
This study aimed to establish the utility of a whole-blood singleplatelet counting (WBSPC) assay, a measure of microaggregation, in monitoring the effects of tirofiban, comparing this with optical aggregometry (OA) and the Ultegra TRAP cartridge system (UTC), measures of macroaggregation. Fifty-nine patients with acute coronary syndrome scheduled for coronary angiography +/angioplasty were studied. WBSPC assay (ADP 0.3-100 µM, Sysmex KX21 analyzer), OA (ADP 20 µM) and UTC were performed: before starting tirofiban; 30 min, 4 and 24 h after starting tirofiban; and 1 and 2h after stopping tirofiban. Thirty minutes after starting tirofiban, there was substantial inhibition of platelet aggregation (40 ± 30%; WBSPC, 2 minutes after addition of ADP 30 µM) and this remained stable at 4 and 24 h. OA (86 ± 17%; inhibition of maximal aggregation,ADP 20 µM) and UTC (93 ± 7%) showed marked inhibition with less inter-individual variation. There was no significant correlation between OA and UTC results (R2 = 0.006), but fair correlation between OA and WBSPC results (R2 = 0.37). Greater inhibition of macroaggregation (OA and UTC) was seen compared to microaggregation (WBSPC) such that WBSPC was more discriminating in the therapeutic range when macroaggregation was often completely inhibited. A WBSPC assay of platelet microaggregation shows promise for monitoring GPIIb/IIIa antagonists.
Keywords: Platelets; tirofiban; whole blood single platelet count; microaggregation